Pemanfaatan Tanah Ulayat Masyarakat Hukum Adat Oleh Investor Dalam Kegiatan Investasi - Firel Estefanus Sahetapy; Alfian Reymon Makaruku; Arie Satrio Sahetapy (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
This research aims to analyze the utilization of Customary Land by Investors in Investment activities. The research method used is Normative Juridical research, using the Statute Approach, Conceptual Approach and Case Approach. The results show that the utilization of customary land in investment activities is closely related to control by the State either directly or indirectly over various natural resources that can reduce the rights of Indigenous Peoples to benefit from available resources. This indirectly illustrates that existing policies and regulations have not placed the dimensions of humanity, justice, and welfare for indigenous peoples as a whole, thus for the smooth implementation of investment activities, permits to investors to operate in the investment object area are important to involve Indigenous Peoples so that contracts can be established between Investors and Indigenous Peoples so that mutual benefits can be realized properly.